2023
DOI: 10.3390/jimaging9020031
|View full text |Cite
|
Sign up to set email alerts
|

NaF-PET Imaging of Atherosclerosis Burden

Abstract: The method of 18F-sodium fluoride (NaF) positron emission tomography/computed tomography (PET/CT) of atherosclerosis was introduced 12 years ago. This approach is particularly interesting because it demonstrates microcalcification as an incipient sign of atherosclerosis before the development of arterial wall macrocalcification detectable by CT. However, this method has not yet found its place in the clinical routine. The more exact association between NaF uptake and future arterial calcification is not fully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Another clinical trial by Joshi et al demonstrated that NaF-PET was more sensitive than FDG-PET in detecting calcified plaque in the coronary arteries of patients with stable angina [8]. Other studies have investigated the utility of NaF-PET/CT for atherosclerosis detection, demonstrating its ability to identify microcalcification prior to macrocalcification [9,10]. This case report demonstrates the utility of NaF-PET/CT imaging in assessing active carotid atherogenesis in a patient with minimal FDG uptake.…”
Section: Introductionmentioning
confidence: 75%
“…Another clinical trial by Joshi et al demonstrated that NaF-PET was more sensitive than FDG-PET in detecting calcified plaque in the coronary arteries of patients with stable angina [8]. Other studies have investigated the utility of NaF-PET/CT for atherosclerosis detection, demonstrating its ability to identify microcalcification prior to macrocalcification [9,10]. This case report demonstrates the utility of NaF-PET/CT imaging in assessing active carotid atherogenesis in a patient with minimal FDG uptake.…”
Section: Introductionmentioning
confidence: 75%
“…To address these limitations, [ 18 F] NaF PET/CT offers a promising imaging modality for the early detection of atherosclerotic plaque formation by identifying changes at the molecular level. Following chemisorption, the 18 F ion exchanges rapidly for the OHion of hydroxyapatite to form fluorapatite. Since hydroxyapatite in macroscopic deposits is internalized, and [ 18 F] NaF is unable to penetrate the crystalline mass, [ 18 F] NaF binding is able to specifically detect new calcifying activity [41].…”
Section: Discussionmentioning
confidence: 99%
“…The hybrid technology of PET and computed tomography (PET/CT) offers an enhanced spatial resolution, along with the capability to visualize molecular alterations throughout the progression of atherosclerosis [16]. The tracers most frequently utilized for this purpose are [ 18 F] fluorodeoxyglucose (FDG) and [ 18 F] sodium fluoride (NaF), which serve as indicators of inflammation and active microcalcification, respectively [17,18]. FDG-PET/CT has previously been correlated with carotid artery inflammation, which cannot be predicted by structural changes alone [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In CKD, 18 F-fluoride activity correlates strongly with bone histomorphometric parameters of skeletal remodeling, with very good diagnostic accuracy for high and low bone turnover [ 144–146 ]. Of interest, 18 F-NaF-PET also identifies sites of active vascular calcification, [ 147 ] and may detect early vascular lesions before arterial wall calcifications can be visualized by CT [ 148 ]. By providing simultaneous assessment of active vascular calcification and skeletal remodeling, 18 F-NaF-PET could offer exciting research possibilities in the field of CKD-MBD.…”
Section: Research Recommendationsmentioning
confidence: 99%